USING CAPTIONED VIDEO CLIP ON GRADE NINE STUDENTS’ VOCABULARY ACHIEVEMENT AT MTs PKP JAKARTA ISLAMIC SCHOOL - Tryanti Abdulrahman, MA (Fakultas Keguruan dan Ilmu Pendidikan | Universitas Islam As-Syafi'iyah, 2017)
By combining an audio and visual media like video can be categorized as an effective multimedia to help teacher in teaching and learning process. Besides, many researchers also have done the research on the use of caption on video to improve students vocabulary. This research is aimed to find out whether or not there is an effect of using captioned video clip on students’ vocabulary achievement. The research samples were taken by means of cluster random sampling from the population, represented in this research by class IX.B as experiment class and IX.C as the control class with total number of samples being 50 students.The research was conducted at MTs PKP Jakarta Islamic School. The research method used in this research was Quasi Experimental research and the design was randomized post-test only control group design. To collect the data, the students were given objective test, numbering 35 items.The findings from the research indicated that there was significant difference that can be seen from the post-test score between the students who received captioned video clip on the experimental class and students who did not receive captioned video clip. It can be seen from the data analysis by using ANOVA that showed Fobserved (56.705) is higher than the critical value of Ftable (at the significant level of 0.05 and df = 1/48), namely 4.04. It can be concluded that there is significant effect of using captionedvideoclipon grade nine students’ vocabularyachievement at MTs PKP Jakarta Islamic School on the academic year 2016/2017.